Penerapan Peran Public Relation Dalam Media Digital PT.Lokatara Karya Indonesia - Janin Islam Khusnul Ainun Nur; Meithiana Indrasari (LPPM Stikosa-AWS, 2022)
The rapid development of technology creates a new media in society, namely digital. Digital media is currently one of the basic needs for the community, especially during the Covid-19 pandemic. Therefore, the public relations profession needs to follow these developments. This research use desciptive qualitative approach. The data is taken from the results of interviews and analysis of digital media PT Lokatara Karya Indonesia. The conclusion shows that the implementation of the public relations role of PT Lokatara Karya Indonesia in Digital Media has not been fully implemented. Of the four role theories proposed by Dozier & Broom, namely expert adviser (expert prescriber), communication facilitator (communications facilitator), problem solving process facilitator (problem solving process facilitator), and communication technician (communications technician), PT Lokatara Karya Indonesia only play two roles actively. The roles that are carried out maximally are Communication Facilitator and Communication Technician.